2021
DOI: 10.1186/s12977-021-00566-0
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 capsid and reverse transcription

Abstract: The viral capsid plays a key role in HIV-1 reverse transcription. Recent studies have demonstrated that the small molecule IP6 dramatically enhances reverse transcription in vitro by stabilizing the viral capsid. Reverse transcription results in marked changes in the biophysical properties of the capsid, ultimately resulting in its breakage and disassembly. Here we review the research leading to these advances and describe hypotheses for capsid-dependent HIV-1 reverse transcription and a model for reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…Reverse transcription of the viral genome may thus lead to breakage of the capsid, once DNA synthesis reaches completion. Mechanical strain from the growing dsDNA as a trigger or driver of the uncoating process has been proposed in several earlier studies (reviewed in [ 26 ]) and is consistent with the detection of a partially broken CA lattice with emanating nucleic acid upon endogenous reverse transcription in isolated capsids in vitro [ 8 ]. It should be noted, however, that HIV-1-based vectors with much shorter genomes effectively transduce nondividing cells.…”
Section: It’s Time To Move On: Separation Of the Viral Genome From The Capsid In The Nucleussupporting
confidence: 62%
“…Reverse transcription of the viral genome may thus lead to breakage of the capsid, once DNA synthesis reaches completion. Mechanical strain from the growing dsDNA as a trigger or driver of the uncoating process has been proposed in several earlier studies (reviewed in [ 26 ]) and is consistent with the detection of a partially broken CA lattice with emanating nucleic acid upon endogenous reverse transcription in isolated capsids in vitro [ 8 ]. It should be noted, however, that HIV-1-based vectors with much shorter genomes effectively transduce nondividing cells.…”
Section: It’s Time To Move On: Separation Of the Viral Genome From The Capsid In The Nucleussupporting
confidence: 62%
“…The capsid contains the viral genome (two vRNA molecules), viral proteins (including NC, reverse transcriptase, integrase, Vpr, among others), and some host proteins, such as APOBEC3 proteins. While early experiments suggested that the capsid disassembles soon after entry into the host cell [1], more recent evidence points to successful viral infection associated with later capsid uncoating after the completion of RT [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Moreover, the intact capsid was found to be transported through the nuclear pore into the nucleus, where RT is completed, followed by uncoating about two hours afterwards in the vicinity of the proviral DNA integration site [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…According to this proposed model, mechanical changes lead to the formation of small ruptures on the core surface. The accumulation of these ruptures on the virus core surface eventually results in loss of the structural integrity of the core and ultimately triggers capsid disassembly [ 68 ]. Our above proposed model for core disassembly was recently supported by a cryo-tomography imaging of virus cores [ 69 ].…”
Section: The Mechanics Of Virus Uncoatingmentioning
confidence: 99%